2023
DOI: 10.3390/v15010155
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection, Chromosome Instability, and Micronucleus Formation

Abstract: Genome integrity is critical for proper cell functioning, and chromosome instability can lead to age-related diseases, including cancer and neurodegenerative disorders. Chromosome instability is caused by multiple factors, including replication stress, chromosome missegregation, exposure to pollutants, and viral infections. Although many studies have investigated the effects of environmental or lifestyle genotoxins on chromosomal integrity, information on the effects of viral infections on micronucleus formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…In our study, basophilic and polychromatic erythroblasts did not exhibit morphologic disturbances in the nucleus, even when exposed to concentrations of 6 and 8 mg/L. This might be due to the fact that the MN can be reincorporated into the main nucleus during subsequent mitosis or destroyed by the autophagy process [71,72].…”
Section: Genotoxicitymentioning
confidence: 42%
“…In our study, basophilic and polychromatic erythroblasts did not exhibit morphologic disturbances in the nucleus, even when exposed to concentrations of 6 and 8 mg/L. This might be due to the fact that the MN can be reincorporated into the main nucleus during subsequent mitosis or destroyed by the autophagy process [71,72].…”
Section: Genotoxicitymentioning
confidence: 42%
“…CCR5Δ32 mutant protein has no function and does not localize on the cell surface [13,70]. The CCR5Δ32 has received much attention due to its protective role against HIV infection and disease progression [20]. Beyond HIV infection, data has shown that this polymorphism is correlated to other conditions such as autoimmune diseases and pathogenic infections [3,71].…”
Section: Discussionmentioning
confidence: 99%
“…As the CCR5Δ32 heterozygous genotype (WT/Δ32) promotes a decreased expression of functional CCR5 on the cell surface, this genotype has slight protection against HIV infection progression. On the other hand, since there is no CCR5 on the cell membrane of people with homozygous genotype, this polymorphism (Δ32/Δ32) shows strong protection against HIV-1 infection [19,20]. CCR5Δ32 genetic variation also leads to a protective effect on Streptococcus pneumoniae [21], Staphylococcus aureus [22], Dengue virus [23], and a severe form of coronavirus disease 2019 (COVID-19) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretrovirals, including nucleoside reverse transcriptase inhibitors, are long recognized to potentially induce genomic instability through damage of nuclear DNA and mtDNA [29,30]. PLWH also exhibit a heightened prevalence of clonal hematopoiesis somatic driver mutations [31,32] and nuclear abnormalities related to genomic instability, specifically nuclear buds and binucleated cells, irrespective of ART status [33]. Although somatic and heteroplasmic blood mtDNA mutations increase with age, the accumulation of blood somatic mtDNA mutation burden is increased in PLWH, particularly with the extent of peak viremia [34].…”
Section: Biological Aging Hallmarksmentioning
confidence: 99%